Global Sequestration Potential of Increased Organic Carbon in Cropland Soils - Zomer, Robert J.; Bossio, Deborah A.; Sommer, Rolf; Verchot, Louis V. (Scientific reports, 2017)
The role of soil organic carbon in global carbon cycles is receiving increasing attention both as a potentially large and uncertain source of CO 2 emissions in response to predicted global temperature rises, and as a natural sink for carbon able to reduce atmospheric CO 2 . There is general agreement that the technical potential for sequestration of carbon in soil is significant, and some consensus on the magnitude of that potential. Croplands worldwide could sequester between 0.90 and 1.85 Pg C/yr, i.e. 26–53% of the target of the “4p1000 Initiative: Soils for Food Security and Climate”. The importance of intensively cultivated regions such as North America, Europe, India and intensively cultivated areas in Africa, such as Ethiopia, is highlighted. Soil carbon sequestration and the conservation of existing soil carbon stocks, given its multiple benefits including improved food production, is an important mitigation pathway to achieve the less than 2 °C global target of the Paris Climate Agreement.